Do approaches to learning affect academic performance of business ethics students? - Mohd Radzi, Zaza Eliza; Ismail, Suhaiza (2012)
Purpose: The objectives of this study are to explore the approaches to learning Business Ethics course adopted by students and to examine the impact of learning approaches on academic performances of Business Ethics course. Methodology: A questionnaire survey was administered to 209 students taking Business Ethics course in a higher learning institution in Malaysia. The Approaches and Study Skills Inventory for Students (ASSIST) was used to assess the learning approaches adopted by students, whilst the study used Final Examination to measure students’ academic performance. Findings: The results indicate that majority students, both male and female groups prefer to use deep approach in studying Business Ethics. The findings also reveal that there are significant positive relationships between deep and strategic approaches and academic performance. On the other hand, there is a significant negative relationship between surface approach and examination result. Research Limitations: The limitation of this study is in terms of the generalisability of the result as the sample size only covers one semester of students taking the course, thus the results may be unrepresentative to other batches of students taking the course in the other semesters. Moreover, this study only used an instrument, ASSIST to examine students’ learning approaches, thus this study may not have access to rich and detailed source of qualitative variation as could be obtained if phenomenography (interview method) is used. Practical/ Theoretical Implications: In terms of theoretical implications, this study contributes to the literatures on approaches to learning by using ASSIST as not many studies to date use ASSIST to measure the students’ approaches to learning. In terms of practical implications, this study may provide guidance to educators to adopt effective teaching strategies to improve student learning by encouraging the right approaches to learning in order to improve students’ academic performance. Keywords: learning approaches, academic performance, ASSIST, gender, ethical judgment